Getting real with real estate investment: Recent developments in Fibra and Firbi - Zaldívar Del Águila, Rodrigo (2017)
FIBRA and FIRBI are newfound investment vehicles in Peru which intend to imitate the form of the USREIT (Real Estate Investment Trusts) establishing a series of benefits to invest in real estate assets. Although the new legislation is ambitious, it is yet perfectible, so that a literal interpretation by the competent authorities (Superintendency of Capital Market– SMV and National Superintendency of Customs and Tax Administration -SUNAT) does not cause such benefits to become unachievable in practice.In the article herein, the authors elaborate an approximation to the FIBRA and FIRBI based on the peruvian regulation, the benefits of the utilization of these mechanisms and the opportunities to improve their regulation.